2021
DOI: 10.3389/fphys.2020.588787
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Adaptations and Enhancement of Physical Performance in Female Basketball Players After 8 Weeks of Plyometric Training

Abstract: The aim of this study was to examine the effects of an 8-week in-season plyometric training (PT) program on the physical performance and neuromuscular adaptations of female basketball players. Twenty-seven elite female basketball players (aged 21.0 ± 2.6 years) were assigned between an experimental group (n = 15) who substituted a part of their usual training with biweekly PT, and a control group (n = 12) who maintained their standard basketball training. Analyses of variance and co-variance assessed changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 56 publications
0
39
1
10
Order By: Relevance
“…The total number of participants across the included studies is 478 (range = 18–101; median = 23), comprising 245 INT (range = 9–50, median = 13) and 233 CON (range = 5–51, median = 11). The majority of the studies used different types of jumps in their training programmes (e.g., bilateral/unilateral vertical and horizontal jumps) ( Kyröläinen et al, 2005 ; Marković et al, 2005 ; Herrero et al, 2006 ; Chelly et al, 2010 ; Fouré et al, 2011 ; Fouré et al, 2012 ; Chelly et al, 2014 ; Chelly et al, 2015 ; McKinlay et al, 2018 ; Fathi et al, 2019 ; Cherni et al, 2020 ). Four studies used one single type of jump such as bilateral countermovemt jump or lateral box jump ( Skurvydas and Brazaitis, 2010 ; Correa et al, 2012 ; Earp et al, 2015 ; Allison et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The total number of participants across the included studies is 478 (range = 18–101; median = 23), comprising 245 INT (range = 9–50, median = 13) and 233 CON (range = 5–51, median = 11). The majority of the studies used different types of jumps in their training programmes (e.g., bilateral/unilateral vertical and horizontal jumps) ( Kyröläinen et al, 2005 ; Marković et al, 2005 ; Herrero et al, 2006 ; Chelly et al, 2010 ; Fouré et al, 2011 ; Fouré et al, 2012 ; Chelly et al, 2014 ; Chelly et al, 2015 ; McKinlay et al, 2018 ; Fathi et al, 2019 ; Cherni et al, 2020 ). Four studies used one single type of jump such as bilateral countermovemt jump or lateral box jump ( Skurvydas and Brazaitis, 2010 ; Correa et al, 2012 ; Earp et al, 2015 ; Allison et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean age across studies ranged from 10.3 to 72.5 years with a median of 20.1 years. Two studies examined the effects of plyometric jump training on hypertrophy in female participants ( Correa et al, 2012 ; Cherni et al, 2020 ), while one study included a mixed intervention group but used a male-only control group ( Skurvydas and Brazaitis, 2010 ). The remaining twelve studies included male participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the published literature, the bench press and squat are the core tests for athletes' fundamental strength, and play essential roles in athletic performances (Hoffman et al, 2007;Patrick et al, 2011), thus these results indicated the significance of the auto-regulation method in enhancing fundamental strength. In addition, competing athletes usually need integrated training to improve athletic performance, such as plyometrics training combined with strength training (Cherni et al, 2021). The autoregulation method may provide flexible training arrangements for athletes to finish their training goals.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, HMB-free acid (HMB-FA) has excellent intestinal absorption and is expected to have immediate effects, but a double-blind, randomized, controlled trial using 3 g of HMB-FA and placebo per day for 6 weeks after resistance training showed that HMB-FA increased muscle strength and the secretory response of growth hormone and IGF-1, which have anabolic effects on protein [15,16,102]. In addition, plyometric training, which has been attracting attention as a method of increasing instantaneous power, such as jumping power [101,103,104], causes muscle damage and inflammatory oxidative stress when the load is high, but HMB-FA intake was shown to prevent these problems [16,[101][102][103]. Thus, HMB may have led to the enhancement and improvement of muscle function, not only by promoting muscle protein synthesis but also by preventing muscle damage through its antioxidant and anti-inflammatory effects.…”
Section: Exercise-induced Muscle Damage Strengthening and Hmbmentioning
confidence: 99%